Paleocene storm-related event beds in the Gaoyou Sag of the Subei Basin, eastern China: A new interpretation for these deep lacustrine sandstones. (February 2021) - Liu, Chao; Jiang, Zaixing; Zhou, Xuewen; Duan, Ye; Lei, Huarui; Wang, Xuying; Atuquaye Quaye, Jonathan
Abstract: Lacustrine storm deposits in hydrocarbon-rich lake basins can be excellent reservoirs; therefore, the identification and interpretation of storm deposits have great significance for future petroleum exploration. Recent progress in facies analysis helps to discriminate the sedimentary effects of combined flow and oscillatory flow in the depositional processes. Through core and well log data and thin-section analysis, the sandy deposits of Paleocene E1 F3 member in the middle part of the Gaoyou Sag, Subei Basin, are interpreted as storm-induced deposits. Petrologic analysis shows that the coarser sediments are mostly fine-grained to silt-sized feldspathic litharenite. Five lithofacies were identified based on core observation, including massive sandstone, cross-bedded sandstone, hummocky cross-stratification (HCS) sandstone, wave rippled sandstone and siltstone, and massive mudstone. Lithofacies associations revealed a storm "sequence" beginning with an erosional surface and then fining upward, indicating hydrodynamic conditions that ranged from gravity flow, unidirectional flow, combined flow to oscillatory flow, which are attributed to storm-related processes. According to the different lithofacies associations and depositional processes, a depositional model including four facies tracts of storm-related deposits are recognized in plane view: (1) storm-induced turbidity channel facies characterized by coarser particles and formed by storm-triggered turbidity current, (2) proximal facies dominated by gravity, unidirectional, and combined flows, (3) transitional facies influenced by all the flow regimes and exhibiting a relatively complete storm "sequence", (4) distal facies formed by low-energy deep-lake turbidity flow. Because storm deposits have petroleum significance in an oil-bearing basin such as Subei Basin, this study provides practical examples and guidance for future hydrocarbon exploration in other ancient lacustrine basins. Highlights: The first to identify tempestite in the Subei Basin in Paleocene Funing Formation. Interpreting depositional process of storms as gravity, unidirectional, combined, and oscillatory flow. Establishing a depositional model for storm-related deposits. Storm-related deposits have great significance for petroleum geology.